Modulating NMDA receptors to treat MK-801-induced schizophrenic cognition deficit: effects of clozapine combining with PQQ treatment and possible mechanisms of action - Xingqin Zhou; Gangming Cai; Shishi Mao; Dong Xu; Xijie Xu; Rongjun Zhang; Zhiwen Yao (BMC Psychiatry, 2020)
Abstract Background Clozapine has remarkable efficacy on both negative and cognitive symptoms of schizophrenia due to its slight activation of NMDA receptor. In fact, much evidence to the contrary. NMDAR is a complex containing specific binding sites, which are regulated to improve negative symptoms and cognitive deficits associated with individuals affected by schizophrenia. PQQ is a powerful neuroprotectant that specifically binds with NMDA receptors in the brain to produce beneficial physiological and cognitive outcomes. The aim of this study was to enhance NMDAR function and improve cognitive ability in schizophrenia by PQQ combined with clozapine. Methods Rats were divided into four groups (n = 5) including control (saline), model (MK-801, 0.5 mg·kg− 1·d− 1), atypical antipsychotic (MK-801 (0.5 mg·kg− 1·d− 1) + Clozapine (1.0 mg·kg− 1·d− 1), and co-agonist NMDA receptor (MK-801 (0.5 mg·kg− 1·d− 1) + Clozapine (0.5 mg·kg− 1·d− 1) + PQQ (1.0 μg·kg− 1·d− 1) group. Each group of rats was injected subcutaneously every day for 6 weeks. Behavior test, including stereotyped behavior, locomotor hyperactivity, learning and memory, was performed. The Western blot assay was performed to analyze the expression of GSK-3β, Akt, NMDAR1, and MGLUR in rat hippocampus. Results Results indicated that clozapine and PQQ combination therapy can improve MK801-induced schizophrenia behavior including stereotyped behavior, locomotor hyperactivity and cognitive impairment. Furthermore, we found that modulating NMDA receptors could ameliorate the memory impairments in Mk-801 induced schizophrenia rats by reducing the expression of NMDAR1 and MGLUR3, decreasing hippocampal tau hyperphosphorylation and inhibiting apoptosis through Akt /GSK-3β signaling pathway. Conclusions These findings suggest that combination therapy for enhancing NMDA receptors may be able to rescue cognition deficit in schizophrenia. More studies are needed to better elucidate these mechanisms.